Critical perspectives on innovation management : the bright and dark sides of innovative firms - Dziurski, Patryk, 1989- (New York, NY : Routledge, 2022)
"Most firms perceive innovation as the best way to grow. However, how it can best be manged is still uncleared. While the number of publications on innovation has skyrocketed over the past two decades, it is still increasingly difficult to gain an overview of its most critical aspects. It has been even more challenging that much has been written about the possible benefits of innovation, but there is still lack of understanding of its downsides at the innovative firm level. This can lead to detrimental effects, such as a lower commitment to innovation, a lack of the effective innovation strategy, inappropriate organizational design that does not enhance innovation, and either a too cautious or too risky approach to innovation. Thus, the book aims to explore the concept of innovation management as well as to identify the bright and dark sides of innovation in innovative firms. A better understanding of the positive and negative effects of product and process innovation expands the knowledge base on innovation management and allows managers to manage innovation in a more efficient and effective manner. This book will be valuable to researchers, academics, managers, and advanced students in the fields of management studies, strategy, and organizational studies"--
OCLC-licensed vendor bibliographic record.
Keywords: Management -- Technological innovations; Business enterprises -- Technological innovations; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Development / Business Development